Surface geoenvironments shape organic matter inputs in iron-ore caves of Carajás, southeastern Amazonia - Luiza Santos Reis; José Tasso Felix Guimarães; Cecília Yuki Gomes de Sá; Enrico Bernard; Luiz Carlos Ruiz Pessenda; Markus Gastauer; Paulo Eduardo de Oliveira (PLoS ONE, 2026)
Cave ecosystems rely heavily on organic matter inputs from the outside to support their trophic networks and biodiversity. In the iron-ore caves of Carajás, southeastern Amazonia, bat guano is a major source of organic matter and integrates signals from the surrounding landscape. Nevertheless, our understanding of the relative contributions from other surface-derived organic matter sources, and how these organic material sources are transported into cave environments is limited. Through a combination of carbon and nitrogen isotope analysis, carbon-to-nitrogen ratio, Bayesian mixing models, and compositional data analysis, the present study estimated for the first time, the contribution of different geoenvironmental units of ferruginous outcrops ( canga ) to cave deposits in four iron-ore caves of Carajás on a preliminary scale. The results indicate a consistent contribution of organic matter derived from poorly drained depressions, particularly swampy fields (median: 41.5–42.9%) and grasslands (median: 8.8–15.1%). These patterns suggest that water infiltration via fractures is an important pathway connecting the surface environment and underground systems, thereby contributing alongside the accumulation of bat guano. This study demonstrates the ecological importance of caves as integrative components of the surrounding landscape and further emphasizes the need to conserve both cave ecosystems and the surface ecosystems that support them by quantifying surface–subsurface connectivity.